B5N10 Nanocarrier Functionalized with Al, C, Si Atoms: A Drug Delivery Method for Infectious Disease Remedy - Mollaamin, Fatemeh; Monajjemi, Majid (LIDSEN Publishing Inc, 2024)
As proof has recommended a close connection between COVID-19 and neurodegenerative disorders, this article aims to investigate the chloroquine (CLQ) drug as the SARS-CoV-2’s primary protease, which can prevent in vitro viral duplication of all diverse experiments to present. CLQ is an anti-viral drug enlarged by Pfizer, which can operate as an orally effective 3C-like protease inhibitor. In this study, CLQ has been assessed for its effectiveness against coronavirus by trapping it within a boron nitride nanocage (B5N10_NC) functionalized with specific atoms for drug delivery. This procedure relies on the principle of direct electron transfer and can be elucidated using density functional theory (DFT) in quantum mechanics methods. It was performed the theoretical method of the B3LYP/6-311+G(d,p) to account for the aptitude of B5N10_NC for grabbing CLQ drug via density of electronic states, nuclear quadrupole resonance, nuclear magnetic resonance, and thermodynamic specifications. Finally, the resulting amounts illustrated that using B5N10_NC functionalized with aluminum (Al), carbon (C), and silicon (Si) for adsorbing CLQ drug towards formation of CLQ@Al–B4N10_NC, CLQ@C–B4N10_NC, CLQ@Si–B4N10_NC might provide the reasonable formula in drug delivery technique which can be fulfilled by quantum mechanics computations due to physicochemical properties of PDOS, NMR, NQR, and IR spectrum. An overview of recent developments in nanocage-based drug delivery systems will be provided, including the design of nanocages and atom-doped nanocages.
Keywords: 3. Good health